PROSES BERPIKIR KREATIF SISWA CLIMBER DALAM PEMECAHAN MASALAH MATEMATIKA PADA MATERI PELUANG - Kurniawan, Indra; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2015)
Abstract: This study aimed to describe the process of creative thinking of students in XI grade IPA-2 SMA Negeri 1 Polanharjo that have AQ climber characteristic in the mathematics problem solving in quiet materials based on Wallas steps, they are: preparation, incubation, illumination and verification. Â The approach t used in this study is qualitative approach. The collecting data in this study used task based on interview method. The process of creative thinking of the climber student in the mathematics problem solving in probability materials, are: (1) in the preparation step, students were enthusiastically when they were given problem solving task. The students explain the case that they knowed and asked in complete and correct with some way, that were: (a) writing the steps and changing into examples, (b) just writing the steps, (c) just changing the case that known in examples; (2) in the incubation step, when the students are understanding probability of event, they: (a)are practising that probability, (b) focus to understand on the problem, (c) less focus to understand on the problem. Then students get an idea by making a complete diagram then multiply the possibilities of occuring on the first and second taking; (3) in the illumination step, student counts probability values are based on complete diagram to sum possibillity of the relevant probability. Students get the new way, that: (a) are the uncomplete diagram and probability formulas, (b) the uncomplete diagram, (c) probability formulas. Students explain the origin of the new way found. Students finish the problem with the new way; (4) in the verification step, students retest all the cases having done befound and corrected the obtained probability values using the old and new way, both of them get the same and correct result.Keywords: creative thinking, problem solving, and climber.